Influence of Time Management Techniques on Teachers’ Job Performance in Private Secondary Schools of Kaduna State, Nigeria - Marcus Garvey Orji; Enobun-Nwidi Patience Enyiamaka; Abdullahi Dangana (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
Many schools face challenges in time management. The objective of this study was to investigate the influence of time management techniques on teachers’ job performance in private secondary schools of Kaduna State, Nigeria. The study is a descriptive survey sampling the opinions of 218 teachers from selected private secondary schools in Kaduna Metropolis. Their opinion was collected using a structured questionnaire. The data obtained was analysed using descriptive and inferential statistics, and the hypotheses tested by means of multiple regression. The findings revealed that time planning has a positive significant impact on teachers’ job performance at a Beta 0.281 and a p value 0.000 at 0.01. The findings also show that setting priority has a positive and significant influence on teachers’ job performance at Beta = 0.288 and a p value 0.001 at 0.01. In addition, the findings also revealed that work scheduling has a positive and significant impact on teachers’ job performance at Beta = 0.401 and p-value level 0.041 at a significance level of 0.05. This implies that time planning, setting priority and work scheduling increase teachers, job performance in secondary schools of Kaduna State. The study concluded that good time management techniques are related to fewer failures, implying a direct relationship between time management techniques and teachers' overall job performance. The study therefore recommended that management and teachers in private secondary schools should continue to maintain good time planning, set priorities, and maintain mastering of work schedules to boost teachers’ job performance in order to achieve quality education in line with SDG 4 and sustainable development goals Agenda 2030 of United Nations.